DIAGNOSIS OF EMERGING DISEASES IN COMMERCIALLY IMPORTANT SHRIMP - R.CAROLINE JEBA; MARIA SHIRLEY (International Journal of Pharma and Bio Sciences, 2015)
As emerging diseases are known to cause a serious setback in shrimp aquaculture due to production and economic losses, it is essential to screen for such diseases. Hence, this study was formulated with the objective to understand the prevalence of emerging diseases affecting commercially important cultured shrimp White spot syndrome virus (WSSV), Infectious hypodermal and hematopoietic necrosis (IHHNV), Acute Hepatopancreatic Necrosis Diseases (AHPND)/ Early Mortality Syndrome(EMS), Enterocytozoon hepatopenaei (EHP), Hepatopancreatic parvovirus (HPV), Yellow head disease (YHV), Monodon baculovirus (MBV).